Rapid assessment of soil quality at the Pasonanca natural park implication for the sustainability of water supply - Ramos, Maria Sheila K.; Casimiro, Jessica Ma. Paz S. (2014)
This study was conducted to assess the sustainability of water supply by examining the ecological integrity of the soil at the Pasonanca Natural Park in Zamboanga city, Philippines by examining the physico-chemical conditions of the surface mineral layer. Stratified random sampling of composited soils were tested for total organic carbon sing Walkley Black method, total Kjehldahl nitrogen and texture analysis using Bouyoucous hydrometer method. The results of the physico-chemical properties of the soil as shown in this study are outside the threshold range required to secure their efficient delivery of the support services to water supply in the watershed. The results are temporart but they suggest potential concenr on the ecological integrity of the Pasonanca Natural Park.
Keywords: Soil testing